Pharmacokinetics of a proposed tocilizumab biosimilar (MSB11456) versus US-licensed tocilizumab: results of a randomized, double-blind, single-intravenous dose study in healthy adults. (3rd April 2023) - Tomaszewska-Kiecana, Monika; Ullmann, Martin; Petit-Frere, Corinne; Monnet, Joëlle; Dagres, Christos; Illes, Andras
ABSTRACT: Background: Tocilizumab, a recombinant monoclonal immunoglobulin G, targets the interleukin-6 receptor. MSB11456 is a proposed tocilizumab biosimilar. Objectives: To assess pharmacokinetic equivalence of intravenous MSB11456 to US-licensed tocilizumab. Research design and methods: In this double-blind, parallel-group, single-dose study, 128 healthy adults were randomized to a single one-hour 8 mg/kg IV infusion of either MSB11456 or US-licensed tocilizumab. Blood samples were collected pre-dose and at regular intervals up to day 48 post-dose. The primary endpoint pharmacokinetic parameter was analyzed using analysis of variance (ANOVA) model on the natural logarithm of the endpoint (AUC0–last ), with treatment as a fixed effect. Immunogenicity and safety data were summarized descriptively. Results: Subjects received either MSB11456 (N = 62) or US-licensed tocilizumab (N = 66). Pharmacokinetic bioequivalence, defined as 90% confidence intervals for the geometric least squares mean ratio entirely contained within the 80.00% to 125.00% equivalence limits, was demonstrated between MSB11456 and US-licensed tocilizumab for the primary and secondary pharmacokinetic endpoints. Anti-drug antibody responses, frequency of neutralizing antibodies against tocilizumab, and safety profiles showed no notable between-treatment differences. Safety was comparable between treatments. Conclusions: Pharmacokinetic similarity of MSB11456 and US-licensed tocilizumab was demonstrated, with comparable immunogenicity and safety profiles, supporting MSB11455 as a biosimilar to US-licensed tocilizumab. The trial is registered at EudraCT, number 2019–003484-22. Plain Language Summary: Tocilizumab is a biologic drug that is prescribed for autoimmune conditions such as rheumatoid arthritis in adults and arthritis in children where the cause is unknown. Because of the high cost of biologic drugs, alternate similar drugs are being designed and tested to ensure that they are as effective and as safe as drugs that are currently available. These new drugs are called biosimilars. MSB11456 is a proposed tocilizumab biosimilar. Our study tested how the pharmacokinetics, immunogenicity, and safety of intravenously administered MSB11456 compared to that of the already approved tocilizumab drug marketed in the US (US-licensed tocilizumab). One hundred and twenty-eight healthy adult volunteers received a one-hour 8 mg/kg intravenous infusion of either MSB11456 or US-licensed tocilizumab in this randomized, double-blind, parallel-group, single-dose study. Blood samples were taken before and at scheduled times during the study, up to 48 days after the first dose for analysis. In this study, we showed that the pharmacokinetics of MSB11456 were equivalent to the US-licensed tocilizumab. The safety and immune response to the drugs were also similar. These findings indicate that MSB11456 can be considered a biosimilar to tocilizumab. Biosimilars can reduce the cost of drugs by increasing competition and improve access to these, generally expensive, treatment options.